Analisis Tata Kelola Teknologi Informasi menggunakan Kerangka Kerja COBIT 5 pada AMIK JTC Semarang - Hadi Hilmawan; Oky Dwi Nurhayati; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
Informations technology has been important elements in an organisation but getting higher information technology implementation cost requires any company or organization to implement an effective operation of information technology. Information technology was expected to help organization in achieveing their business goals and providing not only financial profit but also non-financial profit. To achieve their business goals and ensuring process of information technology works effectively and efficiently, a continuously audit and evaluation of our IT process need to introduced in organization. It will help organization aligning their business process with IT process. One of IT governance framework is COBIT 5. COBIT 5 is a comprehensive framewok that helps organizations to create optimal value from IT by maintaining a balance between realizing benefits and optimizing risk levels and resources use. COBIT 5 enables information and related technology to be governed and managed in a holistic manner for the whole organizations, taking full end to end business and functional area of responsibility, considering the IT-related intererst of internal and external stakeholders.